Image reconstruction algorithm for motion insensitive MR Fingerprinting (MRF): MORF. Issue 6 (6th May 2018) - Mehta, Bhairav Bipin; Ma, Dan; Pierre, Eric Yann; Jiang, Yun; Coppo, Simone; Griswold, Mark Alan
Abstract : Purpose: The purpose of this study is to increase the robustness of MR fingerprinting (MRF) toward subject motion. Methods: A novel reconstruction algorithm, MOtion insensitive MRF (MORF), was developed, which uses an iterative reconstruction based retrospective motion correction approach. Each iteration loops through the following steps: pattern recognition, metric based identification of motion corrupted frames, registration based motion estimation, and motion compensated data consistency verification. The proposed algorithm was validated using in vivo 2D brain MRF data with retrospective in‐plane motion introduced at different stages of the acquisition. The validation was performed using qualitative and quantitative comparisons between results from MORF, the iterative multi‐scale (IMS) algorithm, and with the IMS results using data without motion for a ground truth comparison. Additionally, the MORF algorithm was evaluated in prospectively motion corrupted in vivo 2D brain MRF datasets. Results: For datasets corrupted by in‐plane motion both prospectively and retrospectively, MORF noticeably reduced motion artifacts compared with iterative multi‐scale and closely resembled the results from data without motion, even when ∼54% of data was motion corrupted during different parts of the acquisition. Conclusions: MORF improves the insensitivity of MRF toward rigid‐body motion occurring during any part of the MRF acquisition.